Transportation Utility Fees: Possibilities for the City of Milwaukee - Smith, Lamont; Kurowski, Karen; Duckwitz, Bill; Carlson, Deven (My University, 2007)
Using four evaluation criteria, this report evaluates whether Milwaukee should implement a transportation utility fee (TUF) to fund the operation and maintenance of transportation infrastructure in the city. Under a TUF, transportation infrastructure is treated as a public utility and fees are assigned according to usage. Based on the results of quantitative and qualitative analyses, the authors recommend the adoption of a TUF ordinance in Milwaukee. Such an ordinance would provide an additional revenue source for the City and more equitably distribute the burden of funding transportation infrastructure.